Genotoxicity and subchronic general toxicity assessments of Lactobacillus curvatus WiKim 38 using Sprague-Dawley rats. (June 2021) - Han, Ji-Seok; Back, Seng-Min; Cho, Jae-Woo; Park, Hee Jin; Kim, Woo-Jin; Park, Seong-Hoon; Noh, Jung-Ho; Kim, Yong-Bum; Lee, Byoung-Seok
Abstract: Lactobacillus curvatus WiKim 38 (LCW), isolated from kimchi, has shown novel immunomodulatory and anti-inflammatory properties. In the present study, to obtain data on the safety of LCW, we performed three genotoxicity (bacterial reverse mutation, chromosome aberration, and micronucleus) and two general toxicity (single-dosing and 13-week repeated-dosing) studies. In the genotoxicity assessment, LCW showed no increased reverse mutation for 4 strains of Salmonella typhimurium and a strain of Escherichia coli . In addition, LCW did not induce chromosome aberrations at concentrations up to 5000 μg/mL in cultured Chinese hamster lung (CHL) cells and did not induce an increased frequency of micronuclei in the bone marrow cells of rats at concentrations up to 2000 mg/kg. In the acute toxicity study using Sprague-Dawley (SD) rats, the approximate lethal dose of LCW was determined to be over 5000 mg/kg body weight (b.w.) in both sexes. Finally, in the subchronic toxicity study, no LCW-related adverse effects were observed at concentrations up to 5000 mg/kg b.w./day. Consequently, LCW is considered not to have mutagenic effects, and its no-observed-adverse-effect-level (NOAEL) is 5000 mg/kg b.w., equivalent to approximately 4.71 × 10 9 CFU/kg b.w., suggesting the LCW could be a potential probiotic for humans based on its safety profile. Graphical abstract: Image 1 Highlights: Lactobacillus curvatus WiKim 38 (LCW) showed no genotoxicity based on the study results. In a subchronic toxicity study using rats, the NOAEL for LCW was 4.71 × 10 9 CFU/kg b.w. in both sexes. According to the current safety profile, LCW could be a potential probiotic for humans.